Borders and transit countries: The re-territorialization of Middle East pipelines - Madureira, N. L. (Revista Brasileira de Política Internacional, 2022)
Following the discovery of vast oil reserves in the Persian Gulf region, the Middle East became the main hub for the expansion and development of western pipeline technology. Contrary to the borderless world described in some accounts of globalization, what is observed after 1956 is the establishment of hard political borders, directly under the oversight of national governments, for pipeline deployment with minimal boundary crossings. In the Middle East, this minimal permeability of frontiers entailed fewer risks compared with the uncertainties arising from having to cross several countries: the sovereign state thus seemed the best container for oil transportation. The conclusion puts forward the concept of re-territorialization to explain the multi-level changes that took place, entailing shifts in geography, in business structures and in international relations.